ECONOMIC DEVELOPMENT. DEVELOPMENT STRATEGY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This abstract outlines Uzbekistan's economic development strategy, focusing on recent reforms and initiatives aimed at transforming the economy into a modern, diversified, and competitive system. The document highlights key aspects of Uzbekistan's development strategy, including liberalization efforts, infrastructure development, human capital investment, and regional integration. It discusses the country's goals of diversifying its economy away from traditional sectors like cotton and gas, towards high-value agriculture, manufacturing, and services. Additionally, the abstract touches on Uzbekistan's drive to attract foreign investment and foster trade partnerships, emphasizing the challenges and opportunities in the country's journey towards sustainable economic growth and development.